Penerapan Metode Failure Mode and Effect Analysis (FMEA) dan Fault Tree Analysis (FTA) dalam Menilai Tingkat Risiko Keselamatan dan Kesehatan Kerja (K3) serta Strategi Pencegahan Kecelakaan pada PLTMG Sumbagut 2 Peaker - Jawad, Aod Abdul; Yanto (Teknologi : Jurnal Ilmiah dan Teknologi, 2025)
The Sumbagut Gas Engine Power Plant (PLTMG) operating in Lhokseumawe City, Aceh Province, recorded 19 minor workplace accidents during 2024. In response to this condition, this study aims to identify the risk factors and main causes of workplace accidents in order to develop effective prevention recommendations. This study uses two integrated risk analysis methods. Failure Mode and Effect Analysis (FMEA) is applied to assess and prioritize the level of occupational safety and health (OHS) risks in operational activities. The results of the FMEA analysis indicate that fingers caught in a press machine are the highest risk with a Risk Priority Number (RPN) of 252. Despite having a lower frequency, electrocution incidents are also identified as a critical risk due to their very high potential for fatality. Furthermore, Fault Tree Analysis (FTA) is used to dissect these highest risks, successfully identifying seven (7) basic events that are the root causes of accidents. These causal factors include human error (lack of focus), technical failure (sensors or machine hydraulics), and administrative failure (ignored LOTO procedures). Based on the FMEA and FTA findings, this study presents strategic recommendations to the management of the Sumbagut Gas Processing Plant (GPP) to minimize and prevent future accidents.   Keywords: FMEA, FTA, Occupational Safety and Health